What constitutes medical negligence? - McQuoid-Mason, David J. (SA Heart Journal, 2017)
Medical negligence needs to be distinguished from medical malpractice. Medical malpractice includes both negligent and intentional wrongful acts. Medical negligence occurs when practitioners fail to exercise the standard of skill and care expected of reasonably competent practitioners in their branch of the profession. Negligence refers to behaviour – not a state of mind – and is measured objectively. Medical practitioners may be held vicariously liable for negligent wrongful acts committed by persons employed by them while acting in the scope and course of their employment. Employees are people who can be told what to do and how to do a particular job. Vicarious liability does not apply to independent contractors who can be told what to do but not how to carry out the work. At present unfair exclusion clauses that take away the rights of patients and other healthcare users may be upheld by the courts provided they are not unconstitutional or contrary to public policy. This is likely to change when the Consumer Protection Act (CPA) comes into effect on 1 April 2011. The damages awarded for medical negligence are calculated to put the injured person in the position he or she would have been had the wrongful act or omission not been committed.